INDUSTRIALIZATION AND INDUSTRIAL COMPETITIVENESS IN THE WORLD - Porlles Loarte, José (2006)
The process of world industrialization puts in evidence that Latin America and The Caribbean (ALC) does not count with industrial competitive capacity to face other regions of the world in development, as it is the case of the countries of Eastern Asia, losing opportunities to increase its presence in the current industrial tendencies. The case of Peru is worrying, since it is one of the worst 40 countries classified for the UNIDO in industrial competitive position. With the object of carrying out an xray of the map of the industrial activity in the world and the industrial performance, there have been considered some documents, among others, the last Reports of Industrial Development of the UNIDO.